Personal care product use and lifestyle affect phthalate and DINCH metabolite levels in teenagers and young adults - Stuchlík Fišerová, Petra; Melymuk, Lisa; Komprdová, Klára; Domínguez-Romero, Elena; Scheringer, Martin; Kohoutek, Jiří; Přibylová, Petra; Andrýsková, Lenka; Piler, Pavel; Koch, Holger M; Zvonař, Martin; Esteban-López, Marta; et al. (Environmental research. Section A, 2022)
Humans are widely exposed to phthalates and their novel substitutes, and considering the negative health effects associated with some phthalates, it is crucial to understand population levels and exposure determinants. This study is focused on 300 urine samples from teenagers (aged 12-17) and 300 from young adults (aged 18-37) living in Czechia collected in 2019 and 2020 to assess 17 plasticizer metabolites as biomarkers of exposure. We identified widespread phthalate exposure in the study population. The diethyl phthalate metabolite monoethyl phthalate (MEP) and three di (2-ethylhexyl) phthalate metabolites were detected in the urine of >99% of study participants. The highest median concentrations were found for metabolites of low-molecular-weight (LMW) phthalates: mono-n-butyl phthalate (MnBP), monoisobutyl phthalate (MiBP) and MEP (60.7; 52.6 and 17.6 μg/L in young adults). 1,2-cyclohexanedicarboxylic acid diisononyl ester (DINCH) metabolites were present in 68.2% of the samples with a median of 1.24 μg/L for both cohorts. Concentrations of MnBP and MiBP were similar to other European populations, but 5-6 times higher than in populations in North America. We also observed large variability in phthalate exposures within the study population, with 2-3 orders of magnitude differences in urinary metabolites between high and low exposed individuals. The concentrations varied with season, gender, age, and lifestyle factors. A relationship was found between high levels of MEP and high overall use of personal care products (PCPs). Cluster analysis suggested that phthalate exposures depend on season and multiple lifestyle factors, like time spent indoors and use of PCPs, which combine to lead to the observed widespread presence of phthalate metabolites in both study populations. Participants who spent more time indoors, particularly noticeably during colder months, had higher levels of high-molecular weight phthalate metabolites, whereas participants with higher PCP use, particularly women, tended to have higher concentration of LMW phthalate metabolites.
Keywords: Female; diethylhexylftalát; mladý dospělý; ženské pohlaví; Life Style; životní styl; Adolescent; lidé; Diethylhexyl Phthalate; Environmental Pollutants; Young Adult; Cosmetics; Phthalic Acids; vystavení vlivu životního prostředí; látky znečišťující životní prostředí; kyseliny ftalové; Environmental Exposure; kosmetické přípravky; mladiství; Humans